DNA Condensation Triggered by the Synergistic Self-Assembly of Tetraphenylethylene-Viologen Aggregates and CT-DNA - Saraswathi, Sajena Kanangat; Karunakaran, Varsha; Maiti, Kaustabh Kumar; Joseph, Joshy (Frontiers in Chemistry, 2021)
Development of small organic chromophores as DNA condensing agents, which explores the supramolecular interactions and absorbance or fluorescence-based tracking of the condensation and gene delivery process are in the initial stages. Herein, we report the synthesis and electrostatic/groove binding interaction directed synergistic self-assembly of the aggregates of two viologen functionalized tetraphenylethylene (TPE-V) molecules with CT-DNA and subsequent concentration dependent DNA condensation process. TPE-V molecules differ in their chemical structure by the number of viologen units. Photophysical and morphological studies revealed the interaction of the aggregates of TPE-V in Tris buffer with CT-DNA, which transform the fibrous network structure of CT-DNA to partially condensed “beads on a string” like arrangement with TPE-V aggregates as beads, via electrostatic and groove binding interactions. Upon further increasing the concentration of TPE-V, the “beads on a string” type assembly of TPE-V/CT-DNA complex changes to completely condensed compact structures with 40-50 nm in diameter through the effective charge neutralization process. Enhancement in the melting temperature of CT-DNA, quenching of the fluorescence emission of ethidium bromide/CT-DNA complex and the formation of induced CD signal in the presence of TPE-V molecules supports the observed morphological changes and thereby verify the DNA-condensation abilities of TPE-V molecules. Decrease in the hydrodynamic size, increase in the zeta-potential value with the addition of TPE-V molecules to CT-DNA, failure of TPE-V/Cucurbit[8]uril complex to condense CT-DNA and the enhanced DNA condensation ability of TPE-V2 with two viologen units compared to TPE-V1 with a single viologen unit confirm the importance of positively charged viologen units in the DNA condensation process. Initial cytotoxicity analysis on A549 cancer and WI-38 normal cells revealed that these DNA condensing agents are non-toxic in nature and hence could be utilized for further cellular delivery studies.